Advanced MRI increases the diagnostic accuracy of recurrent glioblastoma: Single institution thresholds and validation of MR spectroscopy and diffusion weighted MR imaging - Kazda, Tomas; Bulik, Martin; Pospisil, Petr; Lakomy, Radek; Smrcka, Martin; Slampa, Pavel; Jancalek, Radim (NeuroImage. Clinical, 2016)
The accurate identification of glioblastoma progression remains an unmet clinical need. The aim of this prospective single-institutional study is to determine and validate thresholds for the main metabolite concentrations obtained by MR spectroscopy (MRS) and the values of the apparent diffusion coefficient (ADC) to enable distinguishing tumor recurrence from pseudoprogression. Thirty-nine patients after the standard treatment of a glioblastoma underwent advanced imaging by MRS and ADC at the time of suspected recurrence - median time to progression was 6.7 months. The highest significant sensitivity and specificity to call the glioblastoma recurrence was observed for the total choline (tCho) to total N-acetylaspartate (tNAA) concentration ratio with the threshold ≥ 1.3 (sensitivity 100.0% and specificity 94.7%). The ADCmean value higher than 1313 × 10(- 6) mm(2)/s was associated with the pseudoprogression (sensitivity 98.3%, specificity 100.0%). The combination of MRS focused on the tCho/tNAA concentration ratio and the ADCmean value represents imaging methods applicable to early non-invasive differentiation between a glioblastoma recurrence and a pseudoprogression. However, the institutional definition and validation of thresholds for differential diagnostics is needed for the elimination of setup errors before implementation of these multimodal imaging techniques into clinical practice, as well as into clinical trials.
Keywords: senioři; Brain Neoplasms; Glioblastoma; Statistics, Nonparametric; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; počítačové zpracování obrazu; Cohort Studies; Middle Aged; ROC Curve; Imaging sensitivity; mužské pohlaví; Choline; Spectroscopy; Glioma; Adult; Aspartic Acid; neparametrická statistika; Diffusion Magnetic Resonance Imaging; ROC křivka; glioblastom; kohortové studie; difuzní magnetická rezonance; ženské pohlaví; kyselina asparagová; Humans; Recurrence; Apparent diffusion coefficient; cholin; lidé středního věku; nádory mozku; Glutamic Acid; kyselina glutamová; Image Processing, Computer-Assisted; dospělí; Female; Aged; lidé; Male